Empirical Analysis of Service Quality on Consumer Satisfaction in Maritime Transportation - Dewa, Adenanthera (LifeSciFi, 2023)
Maritime transportation is a crucial element of a nation's large-scale shipment system, facilitating the movement of goods both within and beyond its borders. Major port cities like Semarang, home to the Semarang Container Terminal (Terminal Peti Kemas Semarang or TPKS), have witnessed a surge in container traffic for imports and exports. In this study, quantitative and qualitative data were collected from 72 respondents through questionnaires, interviews, observations, literature review, and documentation. Based on empirical evidence and a research model involving multiple linear regressions, independent variables, including physical conditions, reliability, responsiveness, assurance, and empathy, individually and collectively have a significant and positive impact on customer satisfaction. Recommendations for TPKS management include enhancing service quality by providing precise services, improving professionalism, enhancing responsiveness, and ensuring clear communication to prevent unexpected costs. This research aids TPKS management in improving service quality and customer satisfaction, with a focus on key dimensions.